EVALUATION OF METABOLIC SYNDROME IN HEALTHY YEMENI POPULATIONS - Alrubaiee, Gamil; Alyahawi, Ali (Universal Journal of Pharmaceutical Research, 2020)
Objective: The metabolic syndrome is characterized by several cardiovascular risk factors and is associated with an increased incidence of diabetes, cardiovascular events and mortality. The prevalence of metabolic syndrome is increasing in epidemic proportions worldwide. The present study aimed to investigate the prevalence of metabolic syndrome and its components in healthy populations in Sana'a, Yemen. Methods: This study was a cross-sectional study conducted from February 2019 to April 2019. A total of 120 healthy populations (40 years≤ old) were selected. The study protocol was approved by the institutional ethical committee and informed consent was obtained from all the enrolled study patients for their inclusion in the screening and participation in the research. In the present study, the diagnosis of metabolic syndrome based on the American Heart Association/National Heart, Lung, and Blood Institute (AHA/NHLBI) and to a joint statement from several large organizations. Results: In the current study, the presence of more than or equal to any three of the above mentioned factors is required for the diagnosis of metabolic syndrome. The total prevalence of metabolic syndrome among the study subjectswas40.0% (P<0.001) and 62.5% of them were within 40-49 years old. In the present study, there was not statically significant difference between the khat chewing and the metabolic syndrome. According the distribution of metabolic syndrome criteria among subjects with metabolic syndrome, the prevalence of fasting blood glucose (FBG) was the highest (85%). Conclusion: The prevalence of metabolic syndrome among healthy Yemeni populations was very high and it is associated with increased morbidity and mortality. This emphasizes the need for more attention to investigate this condition to decreasing the prevalence of cardiovascular morbidity and mortality in these subjects. Peer Review History: Received 10 October 2019; Revised 6 November; Accepted 30 December; Available online 15 January 2020 Academic Editor: Prof. Dr. Gorkem Dulger , Duzce University, Turkey, gorkemdulger@yandex.com Reviewer(s) detail: Prof. Dr. Hassan A.H. Al-Shamahy , Sana'a University, Yemen, shmahe@yemen.net.ye Dr. Muhammad Shahzad Aslam , Universiti Malaysia Perlis, Malaysia, aslam.shahzad@xmu.edu.my